Psychosocial Factors in Marital Satisfaction among Married couples in Benin-City: An Implication for Couple’s therapy. - AROYEWUN, AFOLABI BUSHURA; ADEYEMO, OLADOTUN SUNDAY; EZEMOKWE, CHINEDU ONYINYE; OYEYEMI, TOLULOPE EVELYN (Advances in Social Sciences Research Journal, 2017)
Abstract Marital satisfaction continues to be a significant phenomenon in the present day marriages. However, there has been a significant increase in the numbers of couples that come for couple’s therapy in the last one year. Therefore, this study on the communication pattern, gender and age on marital satisfaction. 200 married couple was conveniently sampled. Index of Marital satisfaction and Primary Communication Inventory were used to measure marital satisfaction and communication pattern respectively. Chi-square analysis was used to investigate the relationship amongst all the variables. The result showed that there was a significant relationship between gender and marital satisfaction (X2=11.591; df=1; p<0.05), also, there was significant relationship between communication pattern and marital satisfaction (X2=23.683; df=1; p<0.05) while there was no significant relationship between age and marital satisfaction (X2=0.207; df=1; p>0.05). It can be concluded that gender and communication have significant relationships on marital satisfaction and as such should be a focus in couple’s therapy.